Rancang Bangun Sistem Smart Door Lock Menggunakan Mikrokontroler Esp32 Berbasis Internet Of Things (Iot) dan Smartphone Android - Maulana, Ikhlas; Azriadi, Emon; Musrido, Joko (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to design and build smart door lock system using Microcontroller ESP32 based on Internet of Things (IoT) and Smartphone Android which will be installed in one of the study rooms at Pahlawan Tuanku Tambusai University using the Quality Function Deployment (QFD) method which aims to identify and meet the needs and desires of consumers for the resulting product or service. This smart door lock is specially made to improve the security system more optimally, and transforming the use from manual door locks to smart door locks that more ergonomic in following technological developments and advances and expanding the use of internet networks in the field of security systems. The process of manufacture smart door locks based on consumer desires using the QFD method which has been processed using the house of quality (HoQ). it can be seen that the percentage of the highest value or priority for product attributes is “Control the smart door lock system using a smartphone” with a value presentation of 5,643%, followed by “Access the smart door lock using the internet network